2019
DOI: 10.1161/circoutcomes.118.005375
|View full text |Cite
|
Sign up to set email alerts
|

Mortality From Ischemic Heart Disease

Abstract: Background: Ischemic heart disease (IHD) has been considered the top cause of mortality globally. However, countries differ in their rates and there have been changes over time. Methods and Results: We analyzed mortality data submitted to the World Health Organization from 2005 to 2015 by individual countries. We explored patterns in relationships with age, sex, and income and calculated age-standardized mortality rates for each country in addition to crude death rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
300
2
28

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 597 publications
(404 citation statements)
references
References 19 publications
6
300
2
28
Order By: Relevance
“…The "French paradox" is based on epidemiological data from French people who had a low incidence of coronary heart disease despite a high intake of dietary cholesterol and saturated fat. Actually, France is still a country with low coronary heart disease incidence and mortality when incidence and mortality when compared to the USA, UK, or Sweden [12][13][14]. During the same year, the concentration of RES in selected wines was measured [15].…”
Section: Resveratrolmentioning
confidence: 99%
“…The "French paradox" is based on epidemiological data from French people who had a low incidence of coronary heart disease despite a high intake of dietary cholesterol and saturated fat. Actually, France is still a country with low coronary heart disease incidence and mortality when incidence and mortality when compared to the USA, UK, or Sweden [12][13][14]. During the same year, the concentration of RES in selected wines was measured [15].…”
Section: Resveratrolmentioning
confidence: 99%
“…Coronary artery disease (CAD) is one of the leading causes of death [1], and the World Health Organization reported that about 9 million people died from ischemic heart disease in 2016 [2]. With the advent of lipid-lowering therapies represented by statins, cardiovascular events after percutaneous coronary intervention have significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Many large prospective cohort studies have shown that hypertension, hyperlipidemia, diabetes, smoking and obesity are the main risk factors for IHD [20] .…”
Section: Discussionmentioning
confidence: 99%